Kompetisi Gulma dan Tanaman Wortel pada Perlakukan Pupuk Organik dan Effective MicroorganismsÂ® - Utami, Sri -; Rahadian, Rully - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2010)
A weed is a plant that is considered to be nuisance and unwanted plant in human-controlled settings,especially farm field and garden. The weed that grow in surrounding of crop could decrease yield due to competitionoccur between weed and crop on nutrition, sunlight and water. Organic farming system which has been developednowadays is an environmental friendly organic farming system. The objective of this research is to determine weedcompetition on carrot using several kinds of organic fertilizer. Six treatments were used in this research, i.e., greenmanure, combination of green manure and EM, EM alone and control (without manure and EM). The weed wasgrowth together with carrot for 3 months. The parameters are wet weight and dry weight of carrot per meter square.The results show that manuring could increase weed competition which in turn wet weight and dry weight of carrotare decreasing. The highest competition between carrot and weed occurred in the treatment of combination betweenorganic manure which combines with EM. The added EM on organic manure could increase weed competition oncarrot.